2008
DOI: 10.1007/s11854-008-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Two extensions of Lubinsky’s universality theorem

Abstract: Abstract.We extend some remarkable recent results of Lubinsky and LevinLubinsky from [−1, 1] to allow discrete eigenvalues outside σess and to allow σess first to be a finite union of closed intervals and then a fairly general compact set in R (one which is regular for the Dirichlet problem).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 39 publications
0
90
0
1
Order By: Relevance
“…There is a large literature on this. Some recent references are [3], [14], [16], [17], [18], [19], [20], [27], [31].…”
Section: Results 1 Let Be a …Nite Positive Borel Measure With Compactmentioning
confidence: 99%
“…There is a large literature on this. Some recent references are [3], [14], [16], [17], [18], [19], [20], [27], [31].…”
Section: Results 1 Let Be a …Nite Positive Borel Measure With Compactmentioning
confidence: 99%
“…This alone is su¢ cient for universality at x. Subsequently, Totik [26], his student Findley [3], and Simon [22] presented far reaching extensions of this result. For example, Totik showed that the same result holds for regular measures on a general compact subset of the real line, instead of [ 1; 1], and moreover, we may relax the requirement of continuity of w. We only need log w to be integrable in a neighborhood of the points where universality is desired, together with a Lebesgue point type condition on a certain local Szeg½ o function.…”
Section: Introduction and Resultsmentioning
confidence: 97%
“…We will show the analogue of Lemma 3.1 in Simon [Sim08b]. Assume regularity bounds (1.4.1) on the measure dµ.…”
Section: Bounds On the Diagonal Kernelmentioning
confidence: 95%
“…It relates a fundamental object to the sine kernel and implies that the left hand side of (2.5.1) only depends on the continuity and positivity of the measure dη at x 0 and its essential support. Simon [Sim08b] and Totik [Tot] extend this argument to measures with supp ess (dη) = ∪I j a finite union of intervals. In this thesis I adapt all the steps to Schrödinger operators.…”
Section: Christoffel-darboux Formulamentioning
confidence: 99%
See 1 more Smart Citation